Accuracy of p57KIP2 compared with genotyping for the diagnosis of complete hydatidiform mole: protocol for a systematic review and meta-analysis. Issue 1 (December 2016) - Madi, Jose; Braga, Antonio; Paganella, Machline; Litvin, Isnard; Da Ros Wendland, Eliana
Abstract Background Distinguishing hydatidiform moles (HMs) from non-molar specimens and the subclassification of HM are important because complete hydatidiform mole (CHM) is associated with an increased risk of gestational trophoblastic neoplasia. However, diagnosis based solely on morphology has poor interobserver reproducibility. Recent studies have demonstrated that the use of p57KIP2 immunostaining improves diagnostic accuracy for CHM. Methods We will conduct a systematic review of prospective and retrospective studies to evaluate the accuracy of p57KIP2 immunostaining compared with molecular genotyping for the diagnosis of CHM. A high-sensitivity search strategy will be employed in MEDLINE, EMBASE, LILACS, The Grey Literature Report, OpenGrey, OAIster, and Cochrane CENTRAL. Two reviewers will independently screen all identified references for eligibility and extract data. The methodological quality and bias of the included studies will be assessed according to the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool, and the overall quality of evidence will be assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. If a meta-analysis is possible, pooled estimates of sensitivity, specificity, and positive and negative likelihood ratios will be calculated using bivariate random-effects models. Statistical heterogeneity will be evaluated withI 2 statistics and explored through sensitivity analysis. Discussion There is considerable overlap between the histological features of molar and non-molar pregnancies and between complete and partial HMs, which results in significant interobserver variability in the diagnosis of CHM and its mimics. Therefore, molecular techniques are used to correctly diagnosis and treat CHM. However, these molecular diagnostic methods are technically difficult to perform, relatively costly, and unavailable in most pathology laboratories. According to our results, p57KIP2 immunostaining appears to be a practical and accurate adjunct for the diagnosis of CHM and its mimics because this technique is relatively simple, reliable, cost-efficient, and rapid. This systematic review will help to determine whether p57KIP2 immunostaining is an adequate alternative diagnostic test for CHM. Systematic review registration PROSPEROCRD42015024181